Maternal Autogenous Inactivated Virus Vaccination Boosts Immunity to PRRSV in Piglets - Andrew R. Kick; Zoe C. Wolfe; Amanda F. Amaral; Lizette M. Cortes; Glen W. Almond; Elisa Crisci; Phillip C. Gauger; Jeremy Pittman; Tobias Käser (Vaccines, 2021)
Maternal-derived immunity is a critical component for the survival and success of offspring in pigs to protect from circulating pathogens such as Type 2 Porcine Reproductive and Respiratory Syndrome Virus (PRRSV-2). The purpose of this study is to investigate the transfer of anti-PRRSV immunity to piglets from gilts that received modified-live virus (MLV) alone (treatment (TRT) 0), or in combination with one of two autogenous inactivated vaccines (AIVs, TRT 1+2). Piglets from these gilts were challenged with the autogenous PRRSV-2 strain at two weeks of age and their adaptive immune response (IR) was evaluated until 4 weeks post inoculation (wpi). The systemic humoral and cellular IR was analyzed in the pre-farrow gilts, and in piglets, pre-inoculation, and at 2 and 4 wpi. Both AIVs partially protected the piglets with reduced lung pathology and increased weight gain; TRT 1 also lowered piglet viremia, best explained by the AIV-induced production of neutralizing antibodies in gilts and their transfer to the piglets. In piglets, pre-inoculation, the main systemic IFN-γ producers were CD21α+ B cells. From 0 to 4 wpi, the role of these B cells declined and CD4 T cells became the primary systemic IFN-γ producers. In the lungs, CD8 T cells were the primary and CD4 T cells were the secondary IFN-γ producers, including a novel subset of porcine CD8α−CCR7− CD4 T cells, potentially terminally differentiated CD4 TEMRA cells. In summary, this study demonstrates that maternal AIV vaccination can improve protection of pre-weaning piglets against PRRSV-2; it shows the importance of transferring neutralizing antibodies to piglets, and it introduces two novel immune cell subsets in pigs—IFN-γ producing CD21α+ B cells and CD8α−CCR7− CD4 T cells.